Peran TikTok sebagai Media Digital dalam Pembelajaran PAI di SMA Negeri 1 Bondowoso: The Role of TikTok as a Digital Media Platform in Islamic Education Learning at SMA Negeri 1 Bondowoso - Miftahul Jannah; Fitria Ayu Ningsih; Ansori (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
Social media has become one of the sources of religious knowledge for teenagers. The rapid dissemination of information and the wide variety of Islamic content make social media an engaging and practical learning medium. However, not all information circulating on social media can be verified, which may lead to misunderstandings in religious practices. This study aims to determine the extent of the role of social media, particularly TikTok, in shaping teenagers’ religious understanding. The method used in this study was a descriptive qualitative approach, with data collected through interviews and observations involving high school students, Islamic Religious Education (PAI) teachers, and school authorities as the research subjects. The results show that social media provides easy and quick access to religious information and helps teenagers learn Islamic teachings more effectively. On the other hand, there is a risk of misuse of religious content due to misinterpretation, unverified content, and a lack of guidance from knowledgeable parties. In conclusion, TikTok plays an important role in shaping teenagers’ religious understanding. However, digital literacy and proper guidance are needed to ensure that the information obtained is aligned with Islamic values and does not lead to deviant interpretations.